Bonding Strength of Luting Cement to Zirconia-Based Ceramic Under Different Surface Treatments - Mendes, Fabio; Zanini, Mauricio M.; Favarão, Jamille; Camilotti, Veridiana; Sinhoreti, Mario A. C.; Mendonça, Marcio J.; Consani, Simonides (European Journal of Dentistry, 2019)
Objectives The aim of this study was to evaluate the bonding strength of self-adhesive luting cement to zirconia under different surface treatments.Materials and Methods Thirty-two zirconia samples were randomly divided into eight experimental groups based on the surface treatment employed (Control: no surface treatment; PMM: wear with diamond bur; JAT: blasting with glass beads; PMA: wear with a medium-roughness milling machine; Primer: primer application on the surface without treatment; PMM +Primer: PMM treatment plus primer application; JAT+Primer: JAT treatment plus primer application; and PMA+Primer: PMA treatment plus primer application). Cement cylinders were built on the ceramic surfaces, and the groups were subdivided according to the storage time employed (i.e., 24 hours or 60 days). After storage, the samples were subjected to microshear testing.Statistical Analysis The Kruskal–Wallis test followed by the Dunn test was employed for comparison between the groups (p < 0.05).Results The PMM group yielded the optimal results and the mean values increased after both storage times following the primer application. The Control, PMA, and JAT groups gave similar results after 24 hours, while the JAT group gave superior results following primer application over this storage time. After 60 days of storage, all groups gave improved results following chemical treatment with a primer.Conclusion It was concluded that mechanical preparation using the diamond bur followed by primer application significantly improved the bond strength between the ceramic and the luting cement.
Keywords: ceramics; shear strength; dental prostheses; zirconium